ANALISIS HUKUM PUTUSAN HAKIM TERHADAP PELAKU TINDAK PIDANA PEMBAKARAN HUTAN DI PROVINSI RIAU - Enjelina, Martina; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In recent times there have been rampant criminal acts of forest burning that have occurred in Indonesia, especially in Riau Province. The crime of forest burning is currently a very serious problem because it can cause multi-dimensional problems related to economic aspects and the factors that occur due to human activity deliberately burning forests and clearing land. However, the sanctions or punishments given to the accused do not have a deterrent effect on the perpetrators, even though there are many regulations that prohibit the act. In this case the law in the form of rules must be obedient to the law. The purpose of writing this thesis, namely: First, to find out the Application of Criminal Sanctions by Judges Against Perpetrators of Forest Burning in Riau Province Judging from Several Judges 'Decisions, Second, to find out the Judges' Basic Considerations in Imposing Criminal Sanctions Against Perpetrators of Forest Burning in the Province Riau.This research is classified in this type of research as normative legal research or can be called doctrinal legal research. Normative legal research is literature law research. In this normative research, the writer conducts research on legal principles. Research on legal principles is research carried out on legal principles which are benchmarks for behaving or having an appropriate or inappropriate attitude. In this normative research, the writer conducts research on several laws and regulations related to problems or problems.From the results of the research and discussion, it can be concluded that, first, there is no law enforcement for criminal law enforcement to ensnare corporations that are indicated for burning forests and land in Riau; second, the enforcement of criminal law against perpetrators of forest and land burning in Riau province is mostly carried out individually. The perpetrators of forest and land burning in Riau are groups of people, business actors and / or communities.Keywords : Decision of the Judge-Crime-Forest Burning